2017
DOI: 10.18267/j.pep.630
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Income Inequality

Abstract: The aim of this paper is to examine the relationship between inflation and income inequality. The article is mainly theoretical, but considerations presented are illustrated by relevant empirical data. Based on our analysis, we claim that inflation, which accelerated after the collapse of the Bretton Woods system in 1971, could have contributed to the rise in income inequality in the USA since the 1970s. Our article transcends the simple notion of an inflation tax and focuses on other redistributive mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
(29 reference statements)
3
7
0
7
Order By: Relevance
“…The findings of the study found a U-shaped link between long-run inflation and income inequality in all ten countries. Similar findings were reached by Sieron (2017), who examined the relationship between inflation and income inequality in the United States. Based on the theoretical analysis of relevant empirical data, the study found that inflation, which accelerated after the collapse of the Bretton Woods system in 1971, would have contributed to the rise in income inequality in the United States since the 1970s.…”
Section: Introductionsupporting
confidence: 77%
“…The findings of the study found a U-shaped link between long-run inflation and income inequality in all ten countries. Similar findings were reached by Sieron (2017), who examined the relationship between inflation and income inequality in the United States. Based on the theoretical analysis of relevant empirical data, the study found that inflation, which accelerated after the collapse of the Bretton Woods system in 1971, would have contributed to the rise in income inequality in the United States since the 1970s.…”
Section: Introductionsupporting
confidence: 77%
“…Одновременно с этим рост экономической активности повышает прибыль от бизнеса, и если этот источник дохода играет большую роль для богатых, то монетарная политика повысит неравенство, но если активность растет за счет малого бизнеса, которым владеют относительно бедные, то эффект будет обратным. Наконец, в странах с прогрессивным налогообложением инфляция повышает неравенство, увеличивая реальное налогообложение для относительно бедных из-за стабильности номинальных показателей доходов, после которых применяется больший налог (Sieron, 2017a).…”
Section: каналы воздействия монетарной политики на распределение доходовunclassified
“…Пожалуй, единственным исключением среди относительно современных работ, являются работы Сиерона (Sieron, 2017a;Sieron, 2017b). В них автор рассматривает различные каналы воздействия, в том числе частично уже упомянутые выше, но концентрирует внимание именно на эффекте Кантильона, который, в отличие от всех остальных, имеет однонаправленное действие и тем самым позволяет существенно повысить качество анализа монетарной политики.…”
Section: эффект кантильона и его влияние на рост неравенства в сшаunclassified
See 1 more Smart Citation
“…Oznacza to, że część osób otrzymuje nowo wykreowane pieniądze wcześniej od innych, jeszcze przed powszechnym wzrostem cen, co zwiększa ich realny dochód i powiększa majątek. Efekt Cantillona wpływa zatem na podział dochodu w społeczeństwie, oddziałując na poziom nierówności dochodowo-majątkowych (Sieroń, 2017).…”
Section: Teoria Dystrybucji Dochodu I Nierówności Dochodowychunclassified